2015
DOI: 10.3791/53130
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering and Imaging Pathogenesis and Cording of <em>Mycobacterium abscessus</em> in Zebrafish Embryos

Abstract: Zebrafish (Danio rerio) embryos are increasingly used as an infection model to study the function of the vertebrate innate immune system in host-pathogen interactions. The ease of obtaining large numbers of embryos, their accessibility due to external development, their optical transparency as well as the availability of a wide panoply of genetic/immunological tools and transgenic reporter line collections, contribute to the versatility of this model. In this respect, the present manuscript describes the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 41 publications
2
79
0
Order By: Relevance
“…Making targeted genetic deletions are particularly challenging in the R variant due to its extremely high aggregative properties. Herein, we combined the larval zebrafish as a tractable host to study the innate immune response to Mabs (16,17) and the successful achievement of the first deletion mutant in the R background. We demonstrate that the recombineering method (31) can be successfully applied to inactivate MAB_4780 in the R variant, leading to multiple and remarkable in vitro and in vivo phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Making targeted genetic deletions are particularly challenging in the R variant due to its extremely high aggregative properties. Herein, we combined the larval zebrafish as a tractable host to study the innate immune response to Mabs (16,17) and the successful achievement of the first deletion mutant in the R background. We demonstrate that the recombineering method (31) can be successfully applied to inactivate MAB_4780 in the R variant, leading to multiple and remarkable in vitro and in vivo phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…bolletii (15), a subspecies of the Mabs complex. We recently used the zebrafish embryo as a tractable infection model to study, at a spatiotemporal level, the physiopathology of Mabs infection and demonstrated the high propensity of virulent R variant Mabs to produce cords in vivo (16,17). We showed that extracellular cording is an example of morphological plasticity allowing bacteria to escape the host immune system.…”
mentioning
confidence: 99%
“…abscessus sensu stricto strain CIP104536 T (ATCC19977T) carrying pTEC15 (Addgene, plasmid 30174), pTEC27 (Addgene, plasmid 30182) or pTEC19 (Addgene, plasmid 30178) that express green fluorescent protein (Wasabi), red fluorescent protein (tdTomato) or bright far-red fluorescent protein (E2-Crimson), respectively, were prepared and microinjected in zebrafish embryos, according to procedures described earlier [17,55]. Briefly, systemic infections were carried by the injection of 100–200 CFU into the caudal vein of 30 hours post-fertilization (hpf) embryos.…”
Section: Methodsmentioning
confidence: 99%
“…To generate neutrophil depleted-embryos, csf3r translation morpholino (5’-GAAGCACAAGCGAGACGGATGCCA T-3’ ) targeting the csf3r gene was used [31]. For the selective depletion of macrophages into embryos, lipo-clodronate (Lipo-C) [56] was injected into the caudal vein of 24 hpf embryos as previously reported [17,55]. …”
Section: Methodsmentioning
confidence: 99%
“…The increasing success of this vertebrate model relies on unique advantages that motivated its use to increase our knowledge of many viral and bacterial infections (Davis et al, 2002; Prajsnar et al, 2008; Phennicie et al, 2010; Alibaud et al, 2011; Mostowy et al, 2013; Palha et al, 2013). Zebrafish embryos have also recently been exploited to visualize, by non-invasive imaging, the progression and fate of Mabs infection, allowing to observe host-pathogen interactions in a live animal at a high resolution level (Bernut et al, 2015; Figure 1). Methods were specifically adapted for assessing Mabs virulence by measuring distinct parameters, such as embryo survival and bacterial burden and by monitoring the chronology of the infection using video microscopy.…”
Section: Introductionmentioning
confidence: 99%